Synthesis of Some Aryl Azo-Compounds Under Mild Conditions - Fathinejad Jirandehi, Hasan; Mobinikhaledi, Akbar (Asian Journal of Chemistry, 2010)
Some aryl azo compounds 2(a-h) were synthesized by reaction of corresponding aromatic amine and phenol derivatives under mild conditions. The yields of the products after recrysallization from acetic acid were in the order of 65-95 %. IR and 1H NMR spectroscopy and elemental analysis were used for the identification of these compounds.